2013
DOI: 10.1111/bjh.12317
|View full text |Cite
|
Sign up to set email alerts
|

GATA2 mutations in sporadic and familial acute myeloid leukaemia patients with CEBPA mutations

Abstract: GATA2 mutations have recently been reported in acute myeloid leukaemia (AML) patients with CEBPA-double mutations. To explore their impact on this favourable-risk disease, we determined GATA2 status in 153 sporadic AML patients and three members of a germ-line CEBPA-mutant family at AML presentation. Overall, 27% (15/55) CEBPA-double, 16% (7/43) CEBPA-single and 0% (0/55) normal karyotype/CEBPA-wild-type patients were GATA2-mutant. All familial AML patients acquired both a second CEBPA and a GATA2 mutation. CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
34
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 12 publications
(28 reference statements)
3
34
2
2
Order By: Relevance
“…We confirmed that GATA2 mutations were significantly associated with CEBPA dm cases (29%, 4 of 41 sm vs. 25 of 87 dm: Fisher's exact test P 5 0.022). In contrast to previous reports [5,8], we have detected GATA2 mutations in CEBPA sm cases at a small frequency of 4% as has Green et al [9] (Table 2).…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…We confirmed that GATA2 mutations were significantly associated with CEBPA dm cases (29%, 4 of 41 sm vs. 25 of 87 dm: Fisher's exact test P 5 0.022). In contrast to previous reports [5,8], we have detected GATA2 mutations in CEBPA sm cases at a small frequency of 4% as has Green et al [9] (Table 2).…”
contrasting
confidence: 99%
“…They were specifically associated with CEBPA sm cases (12 of 40 sm vs. 0 of 78 dm, P < 0.0001) and mutually exclusive of GATA2 mutations (12 of 93 GATA2 wild-type vs. 0 of 25 GATA2 mutated, P < 0.0001). Previous reports found no co-occurrence of FLT3-ITD with GATA2 mutations [5,9]. In contrast to our finding using a larger cohort of CEBPA mutated patients, we have detected three GATA2 mutated cases within 10 FLT3-ITD positive patients (30%).…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…13,14 Gene expression studies have shown that CEBPA bi samples, but not specimens with CEBPA monoallelic mutations, have a distinctive gene expression profile (GEP), [15][16][17][18] and analyses of small series indicated a possibility that this profile is shared by some atypical CEBPA bi AML. 15 Mutations in genes such as GATA2, WT1, and TET2 have been described thus far in CEBPA bi specimens, [19][20][21][22] including 6 specimens reported in The Cancer Genome Atlas cohort. 7 We previously used comparative transcriptomic approaches to report the mutational and transcriptional landscapes of MLL,…”
mentioning
confidence: 99%